Performance of Islamic banks: do the frequency of Sharīʿah supervisory board meetings and independence matter? - Abdalmuttaleb M. A. Musleh Al-Sartawi (ISRA International Journal of Islamic Finance, 2019)
Purpose: This paper aims to investigate the relationship between the composition of Shariʿah supervisory boards (independence and frequency of meetings) and the performance of Islamic banks in the Gulf Cooperation Council (GCC) countries. Design/methodology/approach The study developed a multiple linear regression model, and data were collected from the annual reports of 48 standalone Islamic banks listed in the GCC countries covering the period between 2013 and 2017. Findings The results showed a statistically significant and negative relationship between the composition of the Sharīʿah supervisory boards and the performance of Islamic banks. Research limitations/implications As the current study used only one indicator, that is Return on Assets to measure performance, it is recommended to expand the framework of this study, through the addition of market-based performance indicators such as Tobin's Q. Practical implications This study recommends the GCC countries to follow a more proactive Sharīʿah governance model to strengthen their frameworks from both regulatory and non-regulatory aspects. Originality/value The study contributes to the Sharīʿah governance and Islamic banking literature relating to the GCC countries as previous studies gave no attention to the composition of Sharīʿah supervisory boards.
Keywords: 330; Sharīʿah governance; Sharīʿah supervisory board independence; Sharīʿah supervisory board frequency of meetings; Performance; Islamic banking